Yahoo Web Search

  1. Ads
    related to K.C
  1. Sort by

  1. ... of n people chosen k at a time. C(n,k) = n! / (k! (n-k)!) C(10,3) = 10! / (3! 7!) = 120 I have trouble remembering the formula, so...

    4 Answers · Science & Mathematics · 07/10/2019

  2. ... general formula for exactly k successes is: P(X = k) = C(n,k) * p^k * q^k n : number of trials (e.g. 5 flips) k...

    1 Answers · Science & Mathematics · 14/09/2019

  3. ...n - k)! k!] That would mean: C(n, n - k) = n! / [(n - (n-k))! (n - k)!] C(n, n - k) = n! / [k! (n - k)!] C(n, n - k) = n! / [(n - k)! k!] Hence...

    6 Answers · Science & Mathematics · 12/09/2019

  4. ...atm is the atmospheric concentration, we would model this as: dC(t)/dt = -k*(C(t) - C_atm) where k is some positive rate constant. Note that the...

    2 Answers · Science & Mathematics · 06/08/2019

  5. ... that it's not true. Maybe you mistyped things? k c(k) 4c(k-1) 0 0 1 1 0 2 3 4 3 7 12 4 15 28 5 31 60

    1 Answers · Science & Mathematics · 25/07/2019

  6. ...k±a)  length of major axis = 2a  co-vertices (h±b,k)  foci (h,k±c), c² = a²-b² Apply your given information...

    4 Answers · Science & Mathematics · 29/05/2019

  7. ...k)  vertices (h,k±a)  co-vertices (h±b,k)  foci (h,k±c), c² = a²-b²   (y-10)²/10² + (x-5)²...

    4 Answers · Science & Mathematics · 21/05/2019

  8. x^2 - kx + 4 = 0 apply the discriminant formula a = 1 , b = - k, c = 4 b^2 - 4ac = 0 (-k)^2 - 4(1)(4) = 0 k^2 - 16 = 0 k^2 = 16 k = √(16) k = 4 answer// x^2 - 4x + 4 = 0 (x - 2)(x - 2) = 0 x = 2

    8 Answers · Science & Mathematics · 19/05/2019

  9. Rules (−k)^2/a^2 - (x-h)^2/b^2 = 1 , c = √(a^2+b^2) vertices (h , k+a) and (h , k-a) Foci (h , k + c) and (h , k - c) the asymptotes y - k = ±(a/b)(x-h)

    1 Answers · Science & Mathematics · 13/05/2019

  1. Ads
    related to K.C
  1. Try asking your question on Yahoo Answers